"A valtz from the land of valtzes!": Dance as a Form of Americanization in Abraham Cahan's Fiction. Issue 3 (2nd September 2018) - Gollance, Sonia
ABSTRACT: This article analyzes American Jewish writer Abraham Cahan's depictions of dance in the context of turn-of-the-century, immigrant dance culture. The protagonists of his 1896 novella Yekl: A Tale of the New York Ghetto and his 1917 novel The Rise of David Levinsky are fascinated with dancing and, moreover, identify dance halls with American-style physicality. The two male characters experience very different problems with the women in their lives, difficulties that Cahan suggests result from their inability to conform to American dance etiquette. These romantic failures give the plots a circular structure, reminiscent of the dances themselves.